THE EFFECT OF THE SKIN PERSONAL HYGIENE MODULES AS HEALTH EDUCATION MEDIA AGAINST KNOWLEDGE IN PREVENTION OF SKABIES - Lono Wijayanti; Nur Ainiyah (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2019)
Background: Scabies is often called body lice caused by mites Sarcoptes scabei. Scabies is often overlooked because it is not life-threatening so the priority for treatment is low, but chronic and severe scabies can cause dangerous complications (Harahap, 2008). This typical boarding disease is very closely related to the culture and values that exist in the Islamic boarding school environment. The students who suffer from scabies have complaints that they often itch at night so they can disturb their rest or sleep at night.Objectives: This study aimed to the effect of the skin personal hygiene modules as health education media against knowledge in prevention of skabies in the Islamic boarding school Roudhotul Muta’alimin Muta’alimat, Jabon Sub-District, Sidoarjo District, East Java Province, Indonesia.Method: The study design was used pre-experiment (one group pretest posttest). The population is all of students who lives in the Islamic boarding school Roudhotul Muta’alimin Muta’alimat, Jabon Sub-District, Sidoarjo District, East Java Province, Indonesia, amounting to 72 students. The sample of this study was 60 students using simple random sampling. The research instruments were skin personal hygiene modules and questionnaires. Data was analyzed using the Wilcoxon Signed Ranks Test.Results: The results showed that the level of knowledge before and after being given health education using the skin personal hygiene module was an increase, based on the Wilcoxon Signed Ranks Test analysis showed a difference with a significant value p = 0,000 and significance level α<0.05.Conclusion: Health education using the skin personal hygiene module had a positive impact on increasing the knowledge of the students at the Islamic boarding school Roudhotul Muta'alimin Muta’alimat Jabon Sidoarjo. Health education through counseling can be used to maintain and improve the health of the students in preventing scabies. Keywords: The skin personal hygiene module, knowledge, health education, Scabies.